Asthenia in primary care; The 3me mnemonic - Atul Dhingra; Nishant Raizada; Sanjay Kalra (Journal of the Pakistan Medical Association)
complaint. Asthenia is a subjective, static feeling of weakness, not necessarily related to effort. We propose a simple algorithm which can help primary care physicians in evaluation and counselling of persons presenting with asthenia. (Table 1). This is equally important in persons with acute symptoms and chronic lifestyle diseases.